2022
DOI: 10.3390/jpm12050728
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Symptoms, Mental Health and Quality of Life after Hospitalization in COVID-19 Patients

Abstract: Patients recovering from novel coronavirus are reporting a variety of symptoms such as cough, dyspnea, myalgia as well as psychological distress and poor quality of life. The aim of this study is to assess quality of life and psychological distress in COVID-19 survivors and the sociodemographic and clinical characteristics that affect COVID-19 survivors’ mental health status and quality of life. A quantitative study was conducted among COVID-19 survivors, who had previously been admitted to the University Hosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 34 publications
0
3
0
1
Order By: Relevance
“…Some studies revealed reduced QoL a few weeks after hospital discharge [14], possibly due to decreased mobility [15]. On the other hand, 145 previously hospitalized Greek patients with COVID-19 reported good QoL compared with the general population; however, only a minority of participants experienced severe disease [16]. Moreover, as was shown in a recent large meta-analysis of more than 500 studies regarding long COVID, only 16% and 10% of them focused on the QoL and work aspects, respectively [17].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies revealed reduced QoL a few weeks after hospital discharge [14], possibly due to decreased mobility [15]. On the other hand, 145 previously hospitalized Greek patients with COVID-19 reported good QoL compared with the general population; however, only a minority of participants experienced severe disease [16]. Moreover, as was shown in a recent large meta-analysis of more than 500 studies regarding long COVID, only 16% and 10% of them focused on the QoL and work aspects, respectively [17].…”
Section: Introductionmentioning
confidence: 99%
“…Este dato es similar a lo reportado en población China en donde se reporta un impacto en el 53 % de la muestra. No obstante, es mayor al 24.7 % reportado en población española por Parrado-González y León-Jariego (2020) y al 11.7 % reportado en población griega por Fradelos et al (2022).…”
Section: Discussionunclassified
“…Each domain was scored on a 0-100 metric scale, with a higher score reflecting better health [15]. A mean score of 50 was considered a normative value for all subscales [16].…”
Section: Medical Outcomes Study 36 -Item Short-form Health Surveymentioning
confidence: 99%